Pengaruh Electronic Word Of Mouth Dan Service Quality Terhadap Motivasi Menggunakan Jasa Pendidikan Pesantren: Peran Brand Image Sebagai Variabel Mediasi Dan Trust Sebagai Variabel Moderasi - Ghasani, Fildzah Aulia; Huda, Nuril (Syntax Corporation, 2025)
This study analyzes the influence of Electronic Word of Mouth (eWOM) and Service Quality on parents' motivation in using Islamic boarding school education services, with Brand Image as a mediating variable and Trust as a moderating variable. The research method used is a quantitative approach with path analysis using SmartPLS 4. Data were obtained from 150 respondents who are parents of Islamic boarding school students. The results show that eWOM is predicted to have a significant positive effect on brand image (β = 0.225; p <0.001), and service quality is also predicted to have a significant positive impact (β = 0.322; p <0.001). Trust is predicted as a moderator that weakens the relationship between eWOM and brand image (β = -0.101; p <0.023) and service quality (β = 0.088; p <0.035) shows a significant predicted influence. In addition, brand image with the results of β = 0.828; p <0.001) has a positive and significant predicted influence on motivation to use Islamic boarding school education services. The influence of eWOM (β= 0.187; p<0.001) and service quality (β= 0.266; p<0.001) on the motivation to use services is predicted to be significant, with brand image acting as a mediator. This study provides a theoretical contribution on the development of the Theory of Planned Behavior in marketing through eWOM and service quality on the motivation of parents to use Islamic boarding school education services for their children. As well as practical contributions for Islamic boarding school managers in marketing strategies, improving services, and building a positive brand image and trust in increasing the motivation of parents to choose Islamic boarding school education for their children.